Modelación y simulación de la operación de generadores que emplean turbinas hidrocinéticas en ríos de bajo caudal - Rivadeneira Moya, Diego Mauricio (2015)
In this thesis project a computational tool that works within the parameters of mathematical models implemented for hydrokinetic turbines analysis, allowing search optimization on the analysis of the operation of electricity generation when using hydrokinetic turbines a low flow river, providing the energy available to SNI. By applying the computer program attempting to resolve quickly and reliably analyzing the electrical power generated by a low flow river, in order to provide electrical power using one or more hydrokinetic turbines to an isolated population or turn interconnect network. This requires knowing own data turbine as technical specifications and data specific to the river as speed, volume, area, depth, etc.